Ketersediaan Ruang Terbuka Hijau (RTH) di Kota Salatiga Tahun 2010-2020 - Rachman, Salsa Yusdanur; Sholeh, Muh. (Geo-Image, 2021)
The effect of increasing population is the increasing demand for land by residents in the city. The need for land by the population continues to increase resulting in a reduction in the area of green open space in the city. The city of Salatiga continues to experience population growth every year and results in higher demand for built-up land. The need for built-up land in Salatiga City makes the green open space area continue to decrease. The minimum amount of green open space in a city is 30% of the total city area. The availability of green open space in Salatiga City has decreased in the past 10 years. In 2010 the total area of green open space availability in Salatiga City was 47.85% and in 2020 the total green open space availability in Salatiga City was 39.54%. In a period of 10 years the area of green open space in Salatiga City has decreased by 8.31% due to the increasing demand for urban land by residents of Salatiga City. Pengaruh dari bertambahnya jumlah penduduk adalah meningkatnya kebutuhan lahan oleh penduduk di kota tersebut. Kebutuhan lahan oleh penduduk yang terus bertambah mengakibatkan berkurangnya area ruang terbuka hijau (RTH) di kota. Kota Salatiga terus mengalami pertumbuhan penduduk setiap tahunnya dan mengakibatkan kebutuhan lahan terbangun semakin tinggi. Kebutuhan lahan terbangun Di Kota Salatiga membuat area ruang terbuka hijau (RTH) terus berkurang. Jumlah minimal ketersediaan ruang terbuka hijau pada suatu kota adalah sebesar 30% dari total wilayah kota. Ketersediaan ruang terbuka hijau di Kota Salatiga mengalami penurunan dalam kurun waktu 10 tahun. Pada tahun 2010 total luas ketersediaan ruang terbuka hijau di Kota Salatiga sebesar 47,85% dan pada tahun 2020 total luas ketersediaan ruang terbuka hijau di Kota Salatiga menjadi sebesar 39,54%. Dalam kurun waktu 10 tahun luas ruang terbuka hijau di Kota Salatiga berkurang sebanyak 8.31% yang diakibatkan oleh meningkatnya kebutuhan lahan perkotaan oleh penduduk Kota Salatiga.